2023
DOI: 10.1051/0004-6361/202244149
|View full text |Cite
|
Sign up to set email alerts
|

The historical active episodes of the disks around γ Cassiopeiae (B0.5 IVe) and 59 Cygni (B1 IVe) revisited

D. Baade,
J. Labadie-Bartz,
Th. Rivinius
et al.

Abstract: The observations of all known major activity phases of the disks around the classical Be stars γ Cas and 59 Cyg with low-mass companions are comprehensively reviewed and purely qualitatively evaluated again, though taking advantage of new insights gained over the past 25 yr into the physics of Be disks. Both stars have exhibited activity cycles in the violet-to-red (V/R) flux ratio of emission lines with two peaks. This activity is indistinguishable from those of the vast majority of Be stars and so probably w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 181 publications
(348 reference statements)
0
2
0
Order By: Relevance
“…The presence of the new companion is probably to blame for the elevated RUWE in Gaia DR3, as well as the nonzero eccentricity of the inner Be + sdO pair, which could have been acquired via dynamical interactions in the hierarchical system. Furthermore, the disk of 59 Cyg has experienced major disk tilts in the past (Hummel 1998;Baade et al 2023), which could have been also caused by the newly found companion.…”
Section: Be + Sdob Binariesmentioning
confidence: 99%
“…The presence of the new companion is probably to blame for the elevated RUWE in Gaia DR3, as well as the nonzero eccentricity of the inner Be + sdO pair, which could have been acquired via dynamical interactions in the hierarchical system. Furthermore, the disk of 59 Cyg has experienced major disk tilts in the past (Hummel 1998;Baade et al 2023), which could have been also caused by the newly found companion.…”
Section: Be + Sdob Binariesmentioning
confidence: 99%
“…By contrast, the disks of 60 Cyg and π Aqr dissipated over periods of roughly 1000 days and 2440 days, respectively (Wisniewski et al 2010), while the disk of 66 Oph has been dissipating for more than 20 yr (Marr et al 2021). Over a few decades, the Be star γ Cas famously underwent two shell phases (Baldwin 1940;Borre et al 2020) where the disk may have been dynamically destroyed (Baade et al 2023) before regaining the disk and remaining relatively stable in recent years (Borre et al 2020).…”
Section: Introductionmentioning
confidence: 99%